ANALYSIS THE EFFECT OF FLEXIBILITY, DEPENDENCE, AND QUALITY RELATIONSHIP TO BROKERS PERFORMANCE WITH INTEGRATION STRATEGY AS INTERVENING VARIABLE (STUDY ON PRINTING BROKERS IN SEMARANG) - Rahman, Fazlur; Sufian, Syuhada; Yuniawan, Ahyar (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2018)
In the printing business, brokers are experiencing fierce competition. Many problems always face by the broker because in the production, brokers do not use their own resources, but integrate with service providers. The purpose of this research is to test and analyze the relation of the attributes of flexibility, dependence, relationship quality and integration strategies toward the printing brokers performance.The research is done to the 133 respondents, which all of them are printing brokers who do production in the Semarang area. Methods of data collection by using questionnaires. The method of data analysis using Structural Equation Modeling (SEM) with AMOS 20 software.The results showed that the flexibility and relationships quality had a positive effect on strategy integration. While the dependence does not affect the strategy integration. And the strategy integration variables have a positive effect on the broker performance.